2014
DOI: 10.1186/1749-7922-9-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an acute care surgery service on timeliness of care and surgeon satisfaction at a Canadian academic hospital: a retrospective study

Abstract: IntroductionIn January 2012 an acute care surgery (ACS) model was introduced at St. Paul’s Hospital, Saskatoon, Saskatchewan. The goal of implementing an ACS service was to improve the delivery of care for emergent, non-trauma surgical patients. We examined whether the ACS model improved wait time to surgery, decreased the proportion of surgeries performed after hours, and shortened post-surgical length of stay. We also assessed whether the surgeons working in an ACS system had higher on-call satisfaction than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 10 publications
3
46
0
Order By: Relevance
“…In addition, a majority of general surgeons reported an improved balance between time spent on call and time available for their elective practices (5). In the SHR, the acute care model in general surgery has decreased surgical wait times, led to fewer after-hours surgeries and improved surgeon satisfaction (6). American studies have demonstrated similar findings (7,8).…”
Section: Introductionsupporting
confidence: 60%
“…In addition, a majority of general surgeons reported an improved balance between time spent on call and time available for their elective practices (5). In the SHR, the acute care model in general surgery has decreased surgical wait times, led to fewer after-hours surgeries and improved surgeon satisfaction (6). American studies have demonstrated similar findings (7,8).…”
Section: Introductionsupporting
confidence: 60%
“…This would also mean that urgent cases are more likely to be done in‐hours, hence reducing the piling up of emergency cases running through the night . A study in Canada found that the introduction of a dedicated half‐day ASU theatre resulted in shorter time to surgery …”
Section: Review Of Gsa 12‐point Planmentioning
confidence: 99%
“…Most studies on EGS have focused on processes and outcomes for appendicitis and cholecystitis. 8,[12][13][14] Although these conditions account for a substantial part of the activity of EGS services, they do not reflect the breadth, intensity or resource consumption of a modern EGS practice. In our national EGS sample, appendicitis and cholecystitis together accounted for only 26% of patients and only 10% of hospital stays.…”
Section: Case MIXmentioning
confidence: 99%
“…There are limited data on the overall case mix of these novel EGS services and their varied structures, processes and outcomes. [6][7][8] The emergence of EGS systems represents an opportunity to understand and improve processes of care that serve this complex, resource-intensive surgical population. More research is required on the true acuity, complexity and diversity of EGS services and systems, as well as on the roles these services play in supporting surgical rescue within acute care health systems.…”
mentioning
confidence: 99%